Public awareness and perception of robotic-assisted surgery: a cross-sectional analysis of sociodemographic influences - Irfan Thalib, Husna; Tahir, Khadijah; Shrouq Amin, Ayesha; Hussein Alabdrabalrasol, Zahra; Kaleem Ather, Sarah; Mahmoud Almurad, Bader; Ahmed Al Nawajha, Sara; Elshora, Ahmed A.; Algethami, Mohammed Ridha; Shaik, Noor Ahmad; Al Bagmi, Salem Sroor (Frontiers in Public Health, 2025)
BackgroundRobotic-assisted surgery (RAS) is increasingly prevalent in Saudi Arabia, yet public awareness and acceptance remain inconsistent. This study aimed to evaluate sociodemographic factors influencing familiarity and perception of RAS among the Saudi population.MethodsAn analytical cross-sectional survey was conducted between November 2024 and April 2025 among 681 adults across all major regions of Saudi Arabia using a convenience sampling strategy. A validated, bilingual (Arabic/English) questionnaire assessed RAS awareness, safety perceptions, and concerns. Descriptive statistics summarized responses, chi-square tests explored associations, and binary logistic regression identified predictors of awareness and perception. Odds ratios (ORs) and 95% confidence intervals (CIs) were reported, with significance set at p < 0.05.ResultsOverall, 27.2% of participants reported familiarity with RAS, and 59.5% expressed safety concerns. Females demonstrated higher familiarity than males (OR = 1.45, 95% CI = 1.05–2.01, p = 0.02), while males were more likely to perceive RAS as unsafe (OR = 0.50, 95% CI = 0.34–0.74, p = 0.001). Saudis were significantly more familiar than non-Saudis (OR = 1.75, 95% CI = 1.16–2.64, p = 0.008). Participants from the Southern region were more likely to perceive RAS as safe (OR = 2.00, 95% CI = 1.22–3.27, p = 0.006).ConclusionThis study identifies demographic predictors of awareness and perception of RAS, underscoring the need for targeted educational campaigns, public health messaging, and integration of RAS into medical curricula. Such strategies can improve trust, reduce misconceptions, and facilitate equitable adoption of advanced surgical technologies in Saudi Arabia.